Bubble-based microrobots enable digital assembly of heterogeneous microtissue modules. (1st April 2022) - Ge, Zhixing; Dai, Liguo; Zhao, Junhua; Yu, Haibo; Yang, Wenguang; Liao, Xin; Tan, Wenjun; Jiao, Niandong; Wang, Zhenning; Liu, Lianqing
Abstract: The specific spatial distribution of tissue generates a heterogeneous micromechanical environment that provides ideal conditions for diverse functions such as regeneration and angiogenesis. However, to manufacture microscale multicellular heterogeneous tissue modules in vitro and then assemble them into specific functional units is still a challenging task. In this study, a novel method for the digital assembly of heterogeneous microtissue modules is proposed. This technique utilizes the flexibility of digital micromirror device-based optical projection lithography and the manipulability of bubble-based microrobots in a liquid environment. The results indicate that multicellular microstructures can be fabricated by increasing the inlets of the microfluidic chip. Upon altering the exposure time, the Young's modulus of the entire module and different regions of each module can be fine-tuned to mimic normal tissue. The surface morphology, mechanical properties, and internal structure of the constructed bionic peritoneum were similar to those of the real peritoneum. Overall, this work demonstrates the potential of this system to produce and control the posture of modules and simulate peritoneal metastasis using reconfigurable manipulation.